2005
DOI: 10.1111/j.1399-3046.2005.00258.x
|View full text |Cite
|
Sign up to set email alerts
|

Sodium ferric gluconate for post‐transplant anemia in pediatric and young adult renal transplant recipients

Abstract: Post-transplant anemia is a widespread problem among pediatric renal transplant recipients. Many clinicians treat post-transplant anemia in a manner similar to treatment of anemia in dialysis patients, including the use of intravenous iron, such as sodium ferric gluconate (SFG). Data on pediatric dosing of SFG are limited to rare small series containing few or no renal transplant recipients. We conducted a retrospective chart review of practice patterns at our institution to evaluate doses used, hemoglobin res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 9 publications
0
7
0
2
Order By: Relevance
“…The mean hemoglobin level increased significantly from 10.1 ± 1.6 to 11.4 ± 2.1 g/dl following ferric gluconate therapy. Adverse events were observed in three children [106]. A recent study by Morii and coworkers showed that oral coadministration of ferrous sulphate markedly decreased the absorption of mycophenolate mofetil in healthy Japanese subjects [107].…”
Section: Iron Therapy After Kidney Transplantationmentioning
confidence: 99%
“…The mean hemoglobin level increased significantly from 10.1 ± 1.6 to 11.4 ± 2.1 g/dl following ferric gluconate therapy. Adverse events were observed in three children [106]. A recent study by Morii and coworkers showed that oral coadministration of ferrous sulphate markedly decreased the absorption of mycophenolate mofetil in healthy Japanese subjects [107].…”
Section: Iron Therapy After Kidney Transplantationmentioning
confidence: 99%
“…Warady et al recommended that the starting dose of IV sodium ferric gluconate (SFG) complex be 1.0 mg/kg, not to exceed 125 mg, with adjustments made according to TSAT and/or serum ferritin levels [52]. Gillespie et al analyzed data from 14 pediatric renal transplant recipients who received SFG for PTA during a 28-month period [56]. Patients received one to six doses of SFG to yield a total dose of 100–1000 mg or 2.7–23.7 mg/kg.…”
Section: Approach To Posttransplantation Anemia Managementmentioning
confidence: 99%
“…In a retrospective case series, Gillespie and Symonds used intravenous ferrous gluconate to treat 15 paediatric and young adult renal transplant recipients and found that doses of up to 250 mg induced a statistically significant increase in mean haemoglobin levels. There were only 4 adverse events reported in 3 patients, all self limiting and none life threatening [8]. However, there are no trials to date comparing the efficacy of intravenous versus oral iron replacement.…”
Section: Introductionmentioning
confidence: 99%